PMI approach in the implementation of photovoltaic systems for self-consumption - FIGUEROA LEON, RUBEN ADRIAN; JULCA VERASTEGUI, LUIS ALBERTO; TABOADA NEIRA, MARTIN; VEGA ANTICONA, ALEXANDER YUSHEPY (LACCEI, 2025)
This work includes the design, management and execution of a photovoltaic picogeneration system using renewable solar energy for home self-consumption under the PMI approach, supported by the VDI 2221 standard, which allowed guaranteeing the technical-economic viability of the system, based on the average consumption. of electrical energy of homes and the solar energy potential of sector #4 of the district of Chimbote, Peru. The engineering design methodology with application of the German standard VDI 2221 and under the validated approach of the PMI, ensured the technical characteristics of assembly, operation and maintenance of the photovoltaic system, satisfying the demand of 2.65 kWh/day by 100%, reducing consumption costs, as well as harmful environmental emissions of 0.016 Ton CO2 annually, having a total budget of S/ 10,466.04 and a cost generation unit of 0.4279 S/ kWh, in addition, a NPV of S/ 2,499.63, an IRR of 8.87%, B/C of 1.239 and a PRI of 12.4 were obtained, so the project is profitable, but in the long term , due to the high initial investment cost, also in the event of possible financing, the project would not be as profitable due to the high interest rates of financial entities.